REALIZATION AND PROSPECTS OF DEVELOPMENT OF SYNERGETIC CAPACITY OF THE HOLDING «BELARUSIAN METALLURGICAL COMPANY» - A. I. Rozhkov; D. L. Konovalov (Литьë и металлургия)
The synergy effect of creation of Belarusian Metallurgical Company holding is described in the article, the analysis of directions of its implementation is provided, the prospects of development of synergy potential are defined. The synergy effect is shown on examples of production of cut knivesforscrap metal forthe entities of holding by other enterprises of holding, production of the grinding forged balls from own metal, testing of bearings of JSC Minsk Bearing Plant at the Belarusian steel work.